Exploring the role of phosphatidylinositol 3-kinase catalytic subunit type 3 on plasmacytoid dendritic cell activation - Antas, Paulo Anselmo Nogueira de (2024)
Plasmacytoid dendritic cells (pDCs) are a subpopulation of dendritic cells specialized in the rapid and massive production of type-I interferon (IFN), upon triggering of their pattern recognition receptors (PRRs). They are crucial for effective immune responses, especially against viruses, while also reported to contribute to anti-tumor immunity if properly stimulated. On the other hand, dysregulation of pDCs activity has been implicated in the pathogenesis of autoimmune disorders and in cancer progression. The precise mechanisms regulating pDCs function are not yet fully understood. Phosphatidylinositol 3-kinase catalytic subunit type 3 (VPS34) is a protein crucial for both macroautophagy and endosomal trafficking, cellular processes that have been shown to influence PRRs activity. VPS34 operates in two different complexes, I and II, generators of phosphatidylinositol 3-phosphate (PI(3)P) at the nascent autophagosome and on early endosome membranes, respectively. However, the exact function of VPS34 on pDC responses has not been deciphered. Thus, the aim of this work was to study the role of VPS34 on pDC activation. For this purpose, a human pDC cell line, CAL-1, was used as a model. Cells were treated with the VPS34 inhibitor VPS34-IN1 in the absence of a stimulus or with concomitant PRR activation, either using the TLR7 agonist CL307 or the STING ligand 2’3’-cGAMP, and their response was analyzed. We found that VPS34-IN1 induces STING-dependent type-I IFN expression in unstimulated CAL-1. On the other hand, treatment with VPS34-IN1 impaired type-I IFN production mediated by TLR7 activation, mostly as a consequence of the disruption of VPS34 complex II/UVRAG-dependent processes. Interestingly, VPS34-IN1 impact on TLR7 signaling was mimicked by inhibition of SGK3, a protein known to be recruited to endosomes by VPS34, where it is activated. In contrast, VPS34-IN1 strongly potentiated STING signaling and subsequent IFN-β production triggered by 2’3’-cGAMP stimulation. This synergy occurred due to inhibition of translation by VPS34-IN1. Overall, the results suggest that VPS34 is involved in the regulation of pDC function, representing a potential target to manipulate the activity of these cells in autoimmune diseases linked to pDC anomalies, or to promote anti-tumor immune responses. In addition, our data indicate that SGK3 is important for efficient TLR7 signaling, which offers new strategies to control autoimmune syndromes driven by TLR7 hyperactivation.